Death-associated protein kinase (DAPK) family modulators: Current and future therapeutic outcomes - Farag, Ahmed Karam; Roh, Eun Joo (WILEY, 2019)
Serine/threonine kinases (STKs) represent the majority of discovered kinases to date even though a few Food and Drug Administration approved STKs inhibitors are reported. The third millennium came with the discovery of an important group of STKs that reshaped our understanding of several biological signaling pathways. This family was named death-associated protein kinase family (DAPK family). DAPKs comprise five members (DAPK1, DAPK2, DAPK3, DRAK1, and DRAK2) and belong to the calcium/calmodulin-dependent kinases domain. As time goes on, the list of biological functions of this family is constantly updated. The most extensively studied member is DAPK1 (based on the publications number and Protein Data Bank reported crystal structures) that plays fundamental biological roles depending on the cellular context. DAPK1 regulates apoptosis, autophagy, contributes to the pathogenesis of Alzheimer's disease, acts as a tumor suppressor, inhibits metastasis, mediates the body responses to viral infections, and regulates the synaptic plasticity and depression. For their biological roles, several DAPKs' modulators have been reported for treatment of many diseases as well as acting as probe compounds to facilitate the understanding of the biological functions elicited by this family. Despite that, the number of reported modulators is still limited and more research needs to be conducted on the discovery of novel strategies to activate or inhibit this family. In this report, we aim at drawing more attention to this family by reviewing the recent updates regarding the structure, biological roles, and regulation of this family. In addition, the small-molecule modulators of this family are reviewed in details with their potential therapeutic outcomes evaluated to help medicinal chemists develop more potent and selective possible drug candidates.
Keywords: PROGRAMMED CELL-DEATH; TUMOR-SUPPRESSOR DAPK; PROLYL ISOMERASE PIN1; PHOSPHATASE 2A PP2A; SMALL-MOLECULE; SERINE/THREONINE KINASE; INDUCED APOPTOSIS; PROMOTER METHYLATION; NMDA RECEPTOR; ZIP KINASE